The Application of Interactive Media Powerpoint to Improve The Ability of Students in Reading on The Text Conclude The Matter - Muhayati, Muhayati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research is to increase of students ability in concluded the reading on the text in Indonesian Language in primary school class III using powerpoint interactive media .The class action is research used by two cycles , with every cycle consisting of one meeting .The stage of each cycle is planing, implementation , observation and reflection .The meeting is about the development of the test is conducted in inferring students reading text . In cycle I students be completed after doing test 40 % and in cycle II students be completed is 80 %.This result indicates that uses the media powerpoint interactive can increase the students especially grade III  Indonesian Language at SDN Pranten 01